1985
DOI: 10.1104/pp.79.3.879
|View full text |Cite
|
Sign up to set email alerts
|

ATP Production by Respiration and Fermentation, and Energy Charge during Aerobiosis and Anaerobiosis in Twelve Fatty and Starchy Germinating Seeds

Abstract: The respiration and fermentation rates were compared in germinating seeds of 12 different cultivated species from five families. In air, fermentation contributes significantly to the energy metabolism only in some species (pea, maize), but is generally negligible when compared to respiration. The fermentation rate under anoxia was related either to the metabolic activity under air or to the adenine nucleotide content of the seeds: it was generally higher in seeds which contain starchy reserves (rice, maize, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 24 publications
(34 reference statements)
5
73
0
3
Order By: Relevance
“…At WC of less than 0.5 g/g, the AEC decreased to 0.4. Similar observations have been made for other plant systems in which the energy metabolism was limited by a total or partial deprivation of O 2 (Pradet and Raymond, 1983;Raymond et al, 1985). In both dry seeds and pollen before imbibition, AEC was approximately 0.2 (Fig.…”
Section: Response Of Respiration and Energy Metabolism To Drying In Csupporting
confidence: 84%
See 1 more Smart Citation
“…At WC of less than 0.5 g/g, the AEC decreased to 0.4. Similar observations have been made for other plant systems in which the energy metabolism was limited by a total or partial deprivation of O 2 (Pradet and Raymond, 1983;Raymond et al, 1985). In both dry seeds and pollen before imbibition, AEC was approximately 0.2 (Fig.…”
Section: Response Of Respiration and Energy Metabolism To Drying In Csupporting
confidence: 84%
“…First, the decrease in diffusion rates during drying of our material could be so large that increasing the O 2 gradient from outside to inside of the tissues will not significantly increase the O 2 flux to the mitochondria and O 2 availability to the COX. Second, previous studies Raymond et al, 1985) have shown that the respiratory metabolism in hydrated seeds is sustained at O 2 partial pressures as low as 0.2 kPa. Furthermore, at 21 kPa, COX is saturated with substrates, judging from the low K m for O 2 (Kariman et al, 1983;Leštan et al, 1993).…”
Section: Impeded O 2 Diffusion Is a Likely Factor Responsible For Thementioning
confidence: 93%
“…The studies carried out during the last 25 years have consensually revealed that plants and their seeds, as most of other organisms under low oxygen tension conditions as those found in flooded or completely waterlogged soils, substitute the fermentative metabolism for the aerobic respiration (Mc Mannon & Crawford 1971, Davies 1980Mocquot et al 1981, Joly & Crawford 1982, 1983, Raymond et al 1985, Joly, 1991, 1994, Crawford 1992, Joly & Brändle 1995, Crawford & Brändle 1996, as observed in the seeds of Inga sessilis.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed, in particular, that mitochondria were damaged and had to be repaired during the germination period to become functional at the time of radicle emergence (13). Because fermentation has a low activity in most germinating seeds under aerated conditions (20), new pathways for ATP synthesis have been sought ( 17).…”
Section: Plant Materialsmentioning
confidence: 99%